In Memoriam - Carmen Bach de Roca; Miguel Gaju-Ricart (Soil Organisms, 2015)
With deep sadness we report that Prof. Sturm of the University of Hildesheim passed away on January 2015 at the age of 86. He was already unwell since 2004. We take the liberty to offer a brief statement of his life and work. Education and work. Prof. Sturm graduated from the University of Mainz in 1954. The theme of his doctoral dissertation was ‘Beiträge zur Ethologie einiger mitteldeutscher Machiliden’. In the following year, he obtained a grant to work with Dr. Schaller on Zygentoma and Protura. In order to know part of the arthropod fauna of the tropics, he spent the years 1955/56 with Dr. Vogel in Colombia. From 1957 to 1959 he worked as a teacher in a secondary school in Bingen, Germany. In 1969/70 he accepted the position of assessor in the high school in Idar-Oberstein and Bad Kreuznach, Germany. In 1960/63 Prof. Sturm was an assistant and teacher at the college of higher education in Oldenburg with Prof. Kelle. From 1963 to 1970 he was a lecturer at the college of higher education (Hochschule) in Koblenz. In 1970 he became a Professor of Biology and Didactics of Biology at the University of Hildesheim (previously the Hochschule of Hildesheim) until his retirement. Simultaneous to his tasks at the University, he also enjoyed working in Latin America at the National University of Colombia in Bogota, especially during the years 1967/69 and 6 months in 1978. His interests mainly focused on ecology, ethology, taxonomy and zoogeography of the Microcoryphia of the Paramo region.